Competencies for ethical learning in university students of nursing and pedagogy. - Amelia Tey Teijón; Ruth Vilà Baños; Miquel Martínez Martín (Universitat Politècnica de València, 2014)
The article presents the results of a study conducted with students from the faculties of Pedagogy and Nursing of the University of Barcelona. It focuses on an analysis of the competencies that may help achieve improved ethical learning among university students. The study first seeks to discover students' perception of the dimensions of self-construction, reflection and conviviality. It then proceeds to compare the two samples and highlight relevant differentials which would appear in the definition of an ethical profile of the students. Design of the research is mixed. The first, more qualitative part, centres on interviews with university lecturers and discussion groups; the second part adopts a quantitative approach based on a study by questionnaire, and presents the results obtained through interpretation of the survey. This instrument, which was given to students in the first and last years of their courses at the faculties of Pedagogy and Nursing, identifies observable behaviours with which university students can identify. This article describes the results obtained from the research and some primary conclusions that may be drawn. Among these and worthy of special note is the general high level of ethical-citizenship competencies shown by students in the sample, though differences in the profiles of the students also appear, related to both the faculty and the year in which they are studying.